Mitral valve myxoma presenting with transient ischemic attack: a case report and review of the literature - Grubb, Kendra J. (J Med Case Rep, 2018)
BACKGROUND: Myxomas account for approximately half of all primary cardiac neoplasms. Most occur in the left atrium and only rarely are attached to the mitral valve, with just over 30 such cases reported in the literature. These neoplasms can manifest with a combination of obstruction of blood flow, systemic embolization, and constitutional symptoms. CASE DESCRIPTION: We present a case of a 32-year-old African American man presenting at an emergency department with symptoms of a transient ischemic attack. Transesophageal echocardiography identified a mass originating from the posterior leaflet of the mitral valve. The mass was surgically resected and histologically classified as a myxoma. He remained asymptomatic during the course of 5-year surveillance. CONCLUSIONS: Few similar cases have been described in the literature. Here we present a review of the diagnosis and surgical management of this rare presentation for mitral valve myxoma.